Does metal transfer affect the tribological behaviour of femoral heads? Roughness and phase transformation analyses on retrieved zirconia and Biolox® Delta composites. (1st May 2016) - Affatato, Saverio; Ruggiero, Alessandro; De Mattia, Jonathan Salvatore; Taddei, Paola
Abstract: Although metal transfer (MTR) has been observed in total hip replacement, little is known about its effects on the wear phenomena of bearing surface materials. This study was aimed at investigating the effects of MTR on the bearing surface of zirconia and Biolox ® Delta ceramic femoral heads, to identify prevalent surface patterns and morphologies as well as to evaluate possible phase changes upon MTR, assessing the monoclinic zirconia content and quantifying the tetragonal → monoclinic zirconia transformation. Selected Biolox ® Delta and zirconia femoral heads retrieved from patients after different implantation periods were analysed using a contact profilometer and micro-Raman spectroscopy. The roughness data showed that MTR significantly changed the contact surface of the coupling in the same manner for zirconia and Biolox ® Delta. The micro-Raman analyses showed that in the border control areas, the Biolox ® Delta retrievals were characterised by significantly higher monoclinic contents values compared to zirconia retrievals. Upon wear, zirconia femoral heads underwent a higher increase in the monoclinic content than Biolox ® Delta. The stress related to MTR appeared a particularly severe condition able to induce the phase transformation. In zirconia retrievals, the tetragonal→monoclinic transformation involved a thinner depth of material compared to Biolox ® Delta.